Turkish financial crisis of 2001: Did politics play any role? - Feridun, Mete (LLC CPC Business Perspectives, 2004)
In the last decade, Turkey followed a managed floating exchange rate regime until the late 1999s. In January 2000, Turkey signed a stand-by agreement with the IMF and began following a stabilization program, which involved implementing a crawling peg exchange rate regime. In February 2001, an argument between Prime Minister Bulent Ecevit and President Ahmet Necdet Sezer over how to fight with public-sector corruption triggered a severe financial crisis leading to a skyhigh overnight rate as much as 6200% in uncompounded terms, and a huge decline in foreign exchange reserves of the Central Bank. Consequently, the exchange rate system collapsed and the Central Bank had no option but allowed the Lira to float freely. This article argues that the political considerations were an important factor behind the crisis of the Turkish Lira in February 2001. To test this hypothesis, a linear probability model based on five conventional macroeconomic indicators, and two political variables spanning the period between 1982 and 2001 is built. Evidence emerges that traditional variables such as domestic credit, money supply, and stock market index, as well as the number of political parties in the government, and the timing of elections are significant in explaining the crisis. Results further suggest that inclusion of political variables in the regression model helped in explaining the crisis better through augmenting the fitness of the regression line.
Keywords: Currency crises; Emerging markets; Financial crises; Linear probability model